TANGGUNGJAWAB PIHAK PENYELENGGARA EVENT KETANGKASAN BERISIKO TERHADAP PARTISIPANNYA: TELAAH PERSPEKTIF HUKUM ASURANSI - Saleh, Mohammad (Universitas Tadulako, 2019)
The title of this thesis â€œThe Responsibility of The Event Organizer Ability at Risk to The Participants: Review the Perspective of Insurance Lawâ€. This thesis aims to know the form of responsibility of event organizer to the participants examined from the perspective of insurance law and to see suitability form of responsibility of event organizers who use insurance with insurance law as stipulated in Insurance Law.In preparing this research, researchers use normative juridical research type, then the approach used is the approach of legislation.The results of this study indicate that the responsibility of the organizer of the car racing event has been implemented in accordance with the provisions of law No. 40 of 2014 on insurance and the implementation of personal accident insurance claims for victims of car racing accident there is no any obstacle, especially in terms of premium payments and claims payments, so that it can be associated with the Insurance Law Number 40 Year 2014.Keywords: Insurance Law, Responsibility, Event Organizer, and Insurance Law Number 40 Year 2014